Penerapan Program Merdeka Belajar Kampus Merdeka Mandiri di SMP Negeri 6 Kupang Tengah: “Pengembangan Bakat Musik Siswa Melalui Kegiatan Paduan Suara Oleh Mahasiswa Pendidikan Musik” - nailiu, roci; Seda, Mariana Susanti; Kaet, Margareta Sofyana Irma; Nenabu, Diro Algorti S.; Hambur, Maksimus; Gewayo, Antonius Mario Ola (Sekolah Tinggi Kesenian Wilwatikta (STKW) Surabaya, 2025)
The Independent Campus Learnin Program (MBKM) provides opportunities for students to provide new knowledge and gain factual experience from places where field activities are carried out in order to improve student competence. This article discusses the MBKM Mandiri program by music education students at Widya Mandira Kupang Catholic University which was implemented at SMP Negeri 6 Kupang with a focus on developing students’ musical talents though choral activities. These activities include planning, team building, routine practice and performances. The results show an increase in students’ talents and interests as well as an increase in students’ self-confidence. The implementation of the Mandiri MBKM program is proof of collaboration to improve arts education.